Penentuan Mut’ah Wanita Karir dalam Pandangan Hukum Positif Indonesia - Sanuri Majana (AL-ISTINBATH : Jurnal Hukum Islam, 2018)
The purpose of this research is to know how to give mut’ah if the divorced woman is a career women; Whether the establishment is the same with ordinary women who are not career women. This research is a library research in which the secondary data were obtained from interviews using literature literature such as the Qur'an and hadith. Research begins by way of describing the description of the problems of the data obtained, then drawn conclusions with inductive techniques.In this article, it can be concluded the determination of mut’ahtalak for career women, that is first, the determination of mut’ahtalak for career woman in positive law view in Indonesia is based on propriety contained in article 160 KHI and applies not only to career woman. Sufficiency is worthy or not the amount for the wife in terms of husband's economic ability. Second, the determination of mut’ah for career woman based on propriety and ability of husband as in article 160 KHI. According to the jurisprudence of the judge,the propriety is reasonable whether or not the number is seen from the aspect of the husband's economic capability as well as the aspect of his wife, and also there are the customs prevailing in the environment of the relevant parties in accordance with surah al-Baqarah verse 236.